Analisis Sales Promotion dan Personal Branding Terhadap Keputusan Pembelian Paket Pernikahan Venrose Wedding Organize di Kota Bandung - Rosie Oktavia Puspita Rini; Tirta Mulyadi; Dimas Akmarul Putera; Aulia Agung Dermawan; Wahyudi Ilham (Journal of Event, Travel and Tour Management, 2022)
This study aims to determine the effect of Sales Promotion and Personal Branding, partially or simultaneously on the decision to purchase a Venrose WO wedding package. This study uses quantitative methods using a sample of 100 respondents. Primary data and secondary data are used as data sources in this study. This study uses the SPSS tool for multiple linear regression analysis. The results showed that Sales Promotion partially had a significant effect on purchasing decisions, Personal Branding partially had a significant effect on purchasing decisions, and Sales Promotion and Personal Branding simultaneously had a very significant effect on purchasing decisions.